Réponses

2013-01-19T19:17:17+01:00

a)si c'est e^x + 2 = 3 => e^x = 1 => x = 0

si c'est e^(x+2) = 3 c'est x+2 = ln3 => x = ln3 - 2

b) 2ln(x) = 1 => lnx = 1/2 => x = e^(1/2)

c) (ex-1)(3ex-4)=0  => e^x = 1       ou e^x = 4/3

                                      x = 0               x = ln(4/3)

d) ln(x²+x+1)=0  => x²+x+1 = 1 => x² + x = 0  => x(x+1) = 0 => x= 0 ou x = -1

 

voilà Alice

 

2013-01-19T19:26:30+01:00

a) ex + 2 = 3

a) ex = 3-2 =1 x = 0

  e(x+2) = 3   c'est x+2 = ln3 => x = ln3 - 2

 

b) 2ln(x) = 1

 lnx = 1/2

 x = e(1/2)

 

c) (ex-1)(3ex-4)=0 

 ex = 1      ex = 4/3

 x= 0               x = ln(4/3)

d) ln(x²+x+1)=0 

x²+x+1 = 1

 x² + x = 0  

 x(x+1) = 0

 x= 0       x = -1

 

voila je suis pas trop sur mais j 'espere t'avoir aider